-13.5=6.3+y

Simple and best practice solution for -13.5=6.3+y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -13.5=6.3+y equation:


Simplifying
-13.5 = 6.3 + y

Solving
-13.5 = 6.3 + y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-1y' to each side of the equation.
-13.5 + -1y = 6.3 + y + -1y

Combine like terms: y + -1y = 0
-13.5 + -1y = 6.3 + 0
-13.5 + -1y = 6.3

Add '13.5' to each side of the equation.
-13.5 + 13.5 + -1y = 6.3 + 13.5

Combine like terms: -13.5 + 13.5 = 0.0
0.0 + -1y = 6.3 + 13.5
-1y = 6.3 + 13.5

Combine like terms: 6.3 + 13.5 = 19.8
-1y = 19.8

Divide each side by '-1'.
y = -19.8

Simplifying
y = -19.8

See similar equations:

| (3xy^2)-(5x^2y)+(3xy)-(2x^2y^2)= | | 5(a+8)=25a | | (25x5)=75-(20/4) | | x^2-10x+y^2+14y=-70 | | W/7.5=48 | | 9x^2-20=-4 | | 9x-4=4x+5.25 | | 5a+40=45*2 | | 3/4x=9/20 | | 1-6r=4-r | | 45x^2+10=0 | | X^2+7x-2=2x-8 | | 2x+6=-7x-1 | | 5t-6=2t^2 | | y=(3x-5)-6x | | 0.08x+0.05(3x+37000)=18290 | | 2x+8+x=x+15 | | -3x+19=-11 | | f(x)=2x^2+11x-24 | | 9x+11x=9y+13y | | -11g+5=-12g+13 | | 11-2(3m-10)=5(4-10) | | sin3.14/3 | | -7h=-11h-20 | | 18wd^3/14w^3d | | 936=(20+x)(30+x) | | 63x9-/14 | | 3+2(3m+4)=20-m | | 6h+h+5=6(3+4)+5 | | 7k+2=9+9k+5 | | 4x=2x+47 | | 4x=3+19 |

Equations solver categories